Israel's Covert Diplomacy in Lebanon - Schulze, Kirsten E. author. aut Link
XIV, 213 p.
Keywords: This book deals with the relations of the Jewish Agency and the State of Israel with the Lebanese Maronites in the period 1920-1984. It is essentially a study of the evolution of Israeli policy towards and the minority alliance with the Maronites. The central argument of the book is that Israel has pursued an active policy of intervention in the domestic politics of Lebanon through the alliance, and thus the book challenges the view of Israel as 'a nation that dwells alone'.